NEDD4: A Promising Target for Cancer Therapy - Ye, Xiantao; Wang, Lixia; Shang, Bingxue; Wang, Zhiwei; Wei, Wenyi (Current Cancer Drug Targets, 2014)
The Neuronally expressed developmentally downregulated 4 (NEDD4), functioning largely as an E3 ubiquitin ligase, has been demonstrated to play a critical role in the development and progression of human cancers. In this review, to understand the regulatory mechanism(s) of NEDD4 as well as the signaling pathways controlled by NEDD4, we briefly describe the NEDD4 upstream regulators and its downstream ubiquitin substrates. Moreover, we further discuss its oncogenic roles in human malignancies. Therefore, targeting NEDD4 could be a potential therapeutic strategy for treatment of human cancers.
Keywords: NEDD4